TINJAUAN KUALITAS HASIL WlRAUSAHA BARU PRODUKSI BAHAN BANGUNAN (BATAKO) ANAK-ANAK PANTI ASUHAN YATIM PIATU BASA MOYUDAN. SLEMAN. YOGYAKARTA - Darmono, Darmono (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2003)
Skill education to support life skill needs to be encouraged for each educationlevel including non-formal education. This is as done by the children in the BASA Orphanage, Moyudan, Sleman, Yogyakarta. that has pioneered new entrepreneur in the  field of  building  material  production  especially concrete block  (batako).  The problems are: (1) How far is the produced concrete block quality viewed on physical and mechanical characteristics?, and (2) Which category is the produced  concrete block viewed on its shear stress?The research was conducted by field survey and laboratory test especially toobserve the shear stress of the produced concrete block. The research samples were defined as recommended by the SII Number 0284-80. 10 test materials for each test types.  The  physical  characteristic  observation  on  the  produced  concrete  blocks includes the tests of: (1) Water absorption, (2) Water content, (3) Specific weight, (4) Outside  appearance,  and  (5)  Volume  weight.  The  observation  on  mechanicalcharacteristic is focused on the shear stress of the produced concrete blocks. All of the research activities were conducted in shaping location and the Building Materials and Testing Laboratory. The data collecting technique applies method of noting all the field and laboratory test results. The data analysis technique was conducted qualitatively by presenting the mean.The research shows that the produced concrete blocks with the ratio of 1 PC :12 Sand. have the mean values of: (1) Water absorption of 12.97%; (2) Water contentof 9.07%; (3) Specific weight of 2.11 gr/crrr' ; and (4) Outside appearances: right angled edges. not defect. and the edge decay of 60% good. Whilst viewed on the mechanical characteristic  especially the  shear  stress. It shows  the  mean value of20.155 kg/cnr', classified as Al quality.Key words:  new entrepreneur,   building  materials,  and orphanage